EFFECT OF MYCOPLASMA GALLISEPTICUM INFECTION ON ND VACCINE IN BROILER CHICKENS UNDER VARIOUS TREATMENTS - Abd, A. K.; Ali, A. J. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study aimed to investigate the effect of Mycoplasma gallisepticum infection on Immune  organs and Immune response of ND vaccine in broiler chickens .210 day- old Broiler chicks were  randomly assigned to seven equal groups as following  G1: control  was not received any treatment, G2: only M. gallisepticum infection, G3: only ND vaccine, G4 ND vaccine and M. gallisepticum infection  , G5: ND vaccine and M. gallisepticum infection and treated with probiotic G6: ND vaccine and M. gallisepticum infection  and  treated with Glycyrrhizic Acid by drinking water, G7 : ND vaccine and M. gallisepticum infection  and treated with tylosin by drinking water. Blood samples were collected at 1st, 5th, 10th, 16th, 25th, 27th and 35th day for immunological tests and histopathological examination of spleen and bursa of fabricious at the result revealed the highest level of the ND antibody titers in G5, G6, G7,G1 and G3 respectively. Histopathological analysis of the spleen organ revealed necrosis in G4, white pulp hyperplasia in G6 and G7 while the lesions of bursa indicate that severe hyperplasia in M. gallisepticum infection group. The study concluded that probiotic and glycyrrhizic acid reduce effect of M. gallisepticum infection on immune response and immune organs.